Community-acquired lower respiratory tract infection due to Serratia rubidaea: A rare and opportunistic pathogen - Peetam Singh; Anita Pandey (MRIMS Journal of Health Sciences)
The genus Serratia belongs to the order enterobacterales consisting of Serratia marcescens as the most common species of clinical importance and non-S. marcescens species including Serratia fonticola, Serratia odorifera, Serratia plymuthica, Serratia liquefaciens, and Serratia rubidaea. Most of these non-S. marcescens species are usually considered as nonpathogenic and rarely reported to be associated with various clinical conditions in humans. S. rubidaea is rarely described as member of the genus Serratia which is naturally found in the environment including soil and water. S. rubidaea has been reported as human pathogen, and its isolation from clinical specimens is rare. S. rubidaea has been reported as an opportunistic pathogen affecting immunocompromised individuals. Only few case reports are available documenting clinical significance of S. rubidaea causing various invasive and life-threatening manifestations. We report four cases of community-acquired lower respiratory tract infection caused by S. rubidaea in immunocompromised patients from a tertiary care teaching institute from Uttar Pradesh, India.